DEMOGRAPHIC TRANSITION, NATURAL MOVEMENT OF THE POPULATION - Dilshoda Inomjonova (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, demography, biological factor, marital status, level of development of the state, the basis of demography and the laws of study, development, demographic processes, the role of women in society, national-ethnic characteristics of the population, birth in the structure of demographic processes important aspects of demography are covered.